2000
DOI: 10.1161/01.cir.102.21.2576
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Immune Complexes in 50-Year-Old Men as a Strong and Independent Risk Factor for Myocardial Infarction

Abstract: This prospective study shows that CICs alone or in combination with autoantibodies against cardiolipin in healthy males at 50 years of age predict subsequent MI between the age of and 70 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…Therefore, for functional assays of MPs, AX or other surface markerbased affinity isolation is highly recommended. 46,47 Our findings also have relevance to nonrheumatologic diseases, such as acute coronary syndrome and sickle cell disease in which the presence of circulating ICs is well documented 48,49 and may cause interference with MP detection.…”
Section: Microparticles and Protein Complexes E45mentioning
confidence: 63%
“…Therefore, for functional assays of MPs, AX or other surface markerbased affinity isolation is highly recommended. 46,47 Our findings also have relevance to nonrheumatologic diseases, such as acute coronary syndrome and sickle cell disease in which the presence of circulating ICs is well documented 48,49 and may cause interference with MP detection.…”
Section: Microparticles and Protein Complexes E45mentioning
confidence: 63%
“…Although many human studies have been published correlating AA and IC to oxidation-specifi c epitopes to anatomic coronary and carotid and peripheral arterial disease ( 8,14 ), the focus of the current analysis was CAD risk prediction. Relatively few studies have evaluated their prognostic value in predicting CAD events and the results have been inconsistent ( 6,10,12,13,32,33 ). Initial studies have shown predictive value ( 10,12,13,33 ), but more recent studies with appropriate size and multivariable adjustment have shown no independent predictive value ( 6,32,34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few studies have evaluated their prognostic value in predicting CAD events and the results have been inconsistent ( 6,10,12,13,32,33 ). Initial studies have shown predictive value ( 10,12,13,33 ), but more recent studies with appropriate size and multivariable adjustment have shown no independent predictive value ( 6,32,34 ). Some of the reasons for these disparate fi ndings may be the lack of power, different methodologies for AA and IC measurement, measurement of either IgG of IgM but not both classes, and heterogeneous patient cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…(24) and involvement of C3 and C5 in endothelium activation and leukocyte recruitment to inflammatory sites have been demonstrated. CICs are known to increase with age and play an important role in the induction of vascular damage, leading to low-grade chronic inflammation of the vascular wall (25). Because C3 is the central molecule in the complement system, the level of C3 was measured in this study and its concentration was found to be the highest in the subjects with LDLcholesterolՆ160 mg/dL.…”
Section: Discussionmentioning
confidence: 94%